ARE ARM AND TRM ANALOGS? THELLIER ANALYSIS OF ARM AND PSEUDO-THELLIER ANALYSIS OF TRM - Yu Y.; Dunlop D.J.; Ozdemir O. (My University, 2003)
We test the possibility of using the pseudo-Thellier method as a means of determining absolute paleointensity. Thellier analysis of anhysteretic remanent magnetization (ARM) and pseudo-Thellier analysis of thermoremanent magnetization (TRM) have been carried out on a large collection of sized synthetic magnetites and natural rocks. In all samples, the intensity of TRM is larger than that of ARM and the ratio R (=TRM/ARM) is strongly grain size dependent. The best-fit slope (bTA) from pseudo-Thellier analysis of TRM shows a linear correlation with R. The ratio bTA/R yielded approximately correct paleointensities, although uncertainties are larger than in typical Thellier-type determinations. For single-domain and multidomain magnetites, alternating field and thermal stabilities of ARM and TRM are fairly similar. However, for ~0.24 μm magnetite, ARM is both much less intense and less resistant to thermal demagnetization than TRM, reflecting different domain states for the two remanences and resulting in severely non-linear Arai plots for Thellier analysis of ARM.
Keywords: TRM; ARM; THELLIER METHOD; PSEUDO-THELLIER METHOD; DEMAGNETIZATION